2020
DOI: 10.1093/pch/pxaa008
|View full text |Cite
|
Sign up to set email alerts
|

Re-imagining the physicians’ role in the assessment of feeding challenges in children with autism spectrum disorder

Abstract: While feeding challenges in autism spectrum disorder (ASD) are prevalent, they continue to pose a significant diagnostic challenge, leading to misdiagnosis and under diagnosis of factors, both contextual and inherent, that may lead to negative health outcomes. Early identification of feeding difficulties in ASD is necessary to minimize negative health outcomes and strained parent–child relationships. Family physicians and paediatricians are positioned to reduce the impact of such disordered feeding behaviours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 14 publications
1
21
0
1
Order By: Relevance
“…It concurs with a study that revealed the most mothers of children with ASD identified this as one of the feeding challenges [40]. Early identification of feeding challenges in ASD is necessary to minimise adverse health outcomes and strained parent-child relationships [41]. Difficulty with food textures due to the sensory problems thus affect food selectivity [42].…”
Section: Theme 3: Challenges In Introducing New Foodsupporting
confidence: 74%
“…It concurs with a study that revealed the most mothers of children with ASD identified this as one of the feeding challenges [40]. Early identification of feeding challenges in ASD is necessary to minimise adverse health outcomes and strained parent-child relationships [41]. Difficulty with food textures due to the sensory problems thus affect food selectivity [42].…”
Section: Theme 3: Challenges In Introducing New Foodsupporting
confidence: 74%
“…Children with ASD and eating problems have complex combinations of medical, nutritional, feeding skills and/or psychosocial issues (Smile et al, 2020). Commonly used terms such as "picky eater", "food refusal" and "food selectivity" seem to imply that these are voluntary behaviours when they are very likely to appear because of unidentified medical, psychological and/or sensorimotor problems that make the process of eating challenging or painful (Williams et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The literature outlines oro-motor difficulties in children with ASD (Nadon et al, 2013) and in children demonstrating oral aversions, avoidance or fear of eating (Goday et al, 2019). Difficulty progressing to challenging food textures, gagging, food loss, poor mouth clearance, swallowing issues or drooling may all be manifestations of poor oro-motor control (Smile et al, 2020;Sharp et al, 2013). In case such difficulties are noticed, assessment of the child's oral motor skills is vital.…”
Section: Oro-motor Abilitiesmentioning
confidence: 99%
“…Sensory sensitivity and selective feeding in children with ASD predisposes them to nutritional inadequacy 13,14 . Children with ASD have been shown to have a preference for carbohydrates and aversion to fruits, whole grains, and vegetables 10 . Significant food selectivity (e.g.…”
Section: Dsm‐5 Diagnostic Criteria For Arfid Inclusion Criteria Exclusion Criteriamentioning
confidence: 99%